Severity effect of methanol toxicity from high pressure reactor / Z A Rashid …[et al.] - Rashid, Z A; Subri, M A; Ahmad, M A; Ahmad Fuad, M F I; Japperi, N S (Universiti Teknologi MARA, 2021)
CO2 hydrogenation to methanol synthesis is one of the effective solutions to mitigate the climate changes and the greenhouse gas emissions. However, the drawbacks of this process needed it to operate at high pressure condition where the possibility of leakage and fatality occur is possible. The simulation of this process was simulated using Aspen HYSYS, ALOHA and Google Earth to analyse the methanol toxicity severity from the high-pressure reactor. The probit will determine the level of the severity. It shows that higher pressure with bigger leakage size may experience high severity for the methanol is achieved the highest severity at 400 bar with the bigger leakage size. As the leakage size and pressure is increasing the exposure of the chemical is increasing, thus increasing the severity to the surrounding.